2193 Shares

July 18, 2019 / By Lee
Question: x + 12 = 2x + 6 I want an answer similar to the way I solved this example problem: 2x - 10 = 24 +10 + 10 2x 34 /2 /2 x = 17

Joisse | 2 days ago
Basically, just do the same thing as what you did in the example. The difference here is that you have to collect all the variables on one side and all the constants on the other. x + 12 = 2x + 6 .-x...........-x 12 = x + 6 -6.........-6 6 = x x =6 Hope this helps!
👍 92 | 👎 2
Originally Answered: Graphing equation question? how would solve this linear equation?
2x + 3(11/3) = 12 3/1 * 11/3 = 33/3 When multiplying, just multiply across, numerator to numerator and denominator to denominator. (I know I put a 1 under the 3, all whole numbers have a 1 under them) (example : 3/1 = 3) or ( lets say 5 in fraction form is 5/1 ) (Another fraction example 2/5 * 3/4 mult across and you get 2 * 3 = 6 and 5 * 4 = 20 answer 6/20 then, simplify and get 3/10) Now simplify 33/3 = 11 2x + 11 = 12 Now subtract 11 from both sides. and you get 2x = 1 2x = 1 Now divide 2 on both sides and you get x = 1/2 ordered pair is (1/2 , 11/3)
Originally Answered: Graphing equation question? how would solve this linear equation?
2x + 3(11/3) = 12 look at 3(11/3) = (3 * 11) / 3 = 11 ( 3/3) = 11 that gives you 2x + 11 = 12 2x = 1 x = 1/2 the point (1/2 , 11/3) is a solution to the equation remember, when you multiply fractions, you multiply the tops and multiply the bottoms if there isn't a bottom for one of the fractions, treat it like 1 3(11/3) = (3/1)(11/3) = (3*11) / (1 * 3) = 33 / 3 = 11

Geena
x + 12 = 2x + 6 Subtract 12 from both sides and get x + 12 −12= 2x + 6−12 → x = 2x −6 Subtract 12 from both sides and get x −2x= 2x −6−2x →−x=−6 and x=6
👍 30 | 👎 -2

Decima
x + 12 = 2x + 6 - 12. -12 x. = 2x - 6 -2x. -2x -x. =. -6 /-1. /-1 x. =. 6
👍 29 | 👎 -6